การปลูกผลึกและการศึกษาลักษณะเฉพาะของสารกึ่งตัวนำคอปเปอร์อินเดียมแกลเลียมไดซีลีไนด์ - ทวี ดีจะมาลา (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
Single crystals of the Culn1x Gax Se2 semiconducting compound were grown from the melt by directional freezing method, using the horizontal Bridgman technique, where X is approximately 0.1 and 0.2. The top free surfaces of all obtained crystals are normally the (112) plane. From EDS analysis of CIGS samples from various parts of the crystal the Ga content tends to decrese from the first to freeze end towards the last to freeze end and the Cu content tends to increase from the first to freeze end towards the last to freeze end. The lattice constants a and c increase while Ga content tends to decrease. The energy gap of about 1.04 eV, where X is approximately 0.1, was obtained from optical absorption measurement. From resistivity measurement at room temperature by Van der Pauw method, we found that the resistivity of crystals grown is in the range from 0.29 to 13.1 Ohm-cm. The hall effect measurement at room temperature indicated that the hall mobility of as-grown crystals are in the range from 6.8 to 51.7 cm2V-1s-1 with p type conductivity. On one sample, hall effect were measured from 100K to 327K, variation of resistivities, where X is approximately 0.1., hall mobilities and their carrier concentrations with temperatures were obtained. The relation between the carrier concentration and temperature agreed with an acceptor level of 72.3 meV ionization above the valence band edge. The change of hall mobilities with temperature was brought about by scattering mechanism, namely, acoustic phonon scattering.